Cancer incidence and mortality attributable to alcohol consumption. Issue 6 (28th October 2015) - Praud, Delphine; Rota, Matteo; Rehm, Jürgen; Shield, Kevin; Zatoński, Witold; Hashibe, Mia; La Vecchia, Carlo; Boffetta, Paolo
Abstract : Alcohol consumption is a major cause of disease and death. In a previous study, we reported that in 2002, 3.6% of all cases of cancer and a similar proportion of cancer deaths were attributable to the consumption of alcohol. We aimed to update these figures to 2012 using global estimates of cancer cases and cancer deaths, data on the prevalence of drinkers from the World Health Organization (WHO) global survey on alcohol and health, and relative risks for alcohol‐related neoplasms from a recent meta‐analysis. Over the 10‐year period considered, the total number of alcohol‐attributable cancer cases increased to approximately 770, 000 worldwide (5.5% of the total number of cancer cases)—540, 000 men (7.2%) and 230, 000 women (3.5%). Corresponding figures for cancer deaths attributable to alcohol consumption increased to approximately 480, 000 (5.8% of the total number of cancer deaths) in both sexes combined—360, 000 (7.8%) men and 120, 000 (3.3%) women. These proportions were particularly high in the WHO Western Pacific region, the WHO European region and the WHO South‐East Asia region. A high burden of cancer mortality and morbidity is attributable to alcohol, and public health measures should be adopted in order to limit excessive alcohol consumption. Abstract : What's new? Public health measures to limit alcohol consumption could prevent cancer. Around the world, almost 40% of people drink alcohol regularly. In 2002, a study revealed that around 4% of cancers resulted from alcohol consumption. To update those figures, the authors collected data on the incidence of certain cancers through 2012, and compared alcohol consumption habits. They found that almost 6% of cancers worldwide could be attributed to alcohol; the percentage varied by region, however, from 7% in the Western Pacific region down to 4% in the Americas resulting from drinking alcohol.